Importance Study of Triangulation Method in Research Methodology - Darwishean, Sayeed Ebrahim; Jawad, Abdul Qahar (Journal of Social Sciences - Kabul University, 2023)
This article examines the importance of triangulation in the academic research method to answer the question "Is triangulation a suitable solution for the Paradigm War in the academic research approaches". The basic goal of this article is to examine the importance of triangulation in the academic research method from the perspectives of paradigm war, paradigm shift, and triangulation. Thus, a theoretical descriptive method was advantageous to meet the set goal for this study. For data collection, secondary sources (e.g. available literature) were used incorporating in the article with a method of Meta-analysis. The theoretical descriptive method describes the phenomena and studies the research topic theoretically and provides a complete picture for a thorough understanding of the problem statement. On the other hand, a Meta-analysis searches for existing data and examines existing sources to find the desired data. The findings of this study showed that the triangulation approach is suitable for a detailed, comprehensive, and complete study of a research topic from the perspective of the application of complementary methods (e.g. deploying different researchers, applying different theories, using different data, and atypical sources. In addition, triangulation increases the internal validity of the research and adds to the value of the research.